PENGARUH KUALITAS LAYANAN APLIKASI MOBILE JKN TERHADAP KEPUASAN INFORMASI PESERTA BPJS KESEHATAN - Fardhoni, Fardhoni; Ananda Yusuff, Andinna; Kamasturyani, Yani; Setyo Dwi Andhini, Citra (Seminar Nasional Bidang Kesehatan, Ekonomi, Pendidikan dan Kemasyarakatan (SINAS TAMPAN), 2020)
Background: To improve services to national health insurance participants, BPJS Health launched the mobile JKN application. Many people who come directly to the BPJS Health office because they do not know the application about the Mobile JKN application, do not understand how to use the application. Purpose: Knowing the effect of the quality of mobile JKN application services on the information satisfaction of BPJS Health participants. Method: The method in this study is a quantitative method with a Cross Sectional design. The population in this study is users of the Mobile JKN Application, the BPJS Health Bandung Branch. The study sample was 94 respondents. Sampling techniques use simple sandom sampling techniques. The statistical test used in this study was the chi-square test (X2). Results: The results of the study were that most respondents stated that the quality of service was good (61.7%), more than half of respondents were dissatisfied (52.1%). There is an influence on the quality of mobile JKN application services on BPJS Health participant information satisfaction (P = 0.004). Conclusion: If the quality of service is good, it is likely that 3.9 times of BPJS Health participants feel satisfied compared to the quality of service is not good.